An ordered platinum alloy powder, a method for preparing the same and use thereof
Patent Information
- Application Number
- CN202611136922.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-30
AI Technical Summary
但是,PtRu合金虽然能够提升抗CO毒化的能力,可当CO超过100ppm以上后,其抗毒化能力无法满足实际应用需求,其性能衰减依然较大,制约了以粗氢为燃料的PEMFC的工程化应用
[0034]在符合本领域常识的基础上,上述各优选条件,可任意组合,即得本发明各较佳实例。
Smart Images

Figure CN122999996A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen oxidation catalytic reaction technology, and in particular to an ordered platinum alloy powder, its preparation method, and its application. Background Technology
[0002] Proton exchange membrane fuel cells (PEMFCs), as highly efficient and zero-carbon emission power generation devices, represent the future direction of clean energy development. Fuel cells primarily use hydrogen and air as fuel, transferring electrons to an external circuit through electrochemical conversion to generate electricity. On the anode side, phosphorus (Pt) is typically used as a catalyst for the hydrogen oxidation reaction (HOR). However, most hydrogen feedstock currently comes from industrial by-products (low cost), which may contain residual impurities such as carbon monoxide (CO). Pt metal has a strong adsorption capacity for CO, which can poison the Pt sites at the anode during fuel cell operation, leading to a gradual decline in performance.
[0003] Therefore, for fuel cell power generation systems that use industrial by-product hydrogen as fuel, developing highly efficient Pt-based catalysts resistant to CO poisoning is crucial for improving the activity and stability of PEMFCs.
[0004] Currently, PtRu alloys are a relatively traditional catalyst system for resisting CO poisoning. Utilizing the synergistic effect of Ru, CO adsorbed on Pt sites is diverted to Ru sites, thereby inhibiting CO poisoning of Pt sites and improving the catalyst's resistance to CO poisoning to some extent. However, although PtRu alloys can improve CO poisoning resistance, when CO exceeds 100 ppm, their resistance cannot meet the requirements of practical applications, and their performance degradation remains significant, restricting the engineering application of PEMFCs using crude hydrogen as fuel. Summary of the Invention
[0005] To address the aforementioned problem of the lack of CO-resistant catalysts, this invention provides an ordered platinum alloy powder that can be used as a catalyst for hydrogen oxidation reaction (HOR) and exhibits excellent CO-resistant capabilities.
[0006] A method for preparing ordered platinum alloy powder includes the following steps: Precursor solution preparation: Vanadium source reagent and platinum source reagent are dissolved in solvent at a V:Pt molar ratio of 1.5-3.5:1, carbon powder is added and dispersed evenly to obtain the precursor solution; Preparation of solid precursor: The solvent of the precursor solution is recovered to obtain a solid precursor; Heat treatment: The solid precursor is heated at 650-750°C. o Heat treatment at C for 1-4 hours yields powder; Pickling: The heat-treated powder is washed in acid, rinsed with water until neutral, and dried to obtain the ordered platinum alloy powder.
[0007] The inventors' research and analysis revealed that the performance degradation of traditional Pt / Ru alloys is due to the random distribution of Pt and Ru atoms within the alloy. Only when PtRu sites are formed can CO overflow occur, thereby inhibiting Pt site poisoning. However, since the alloy is a mixture, Pt-Pt, Ru-Ru, and Pt-Ru formations can all occur randomly, resulting in low anti-poisoning efficiency. Therefore, reducing CO adsorption at Pt sites by addressing the Pt atom coordination environment is crucial for preparing highly efficient CO-poisoning resistant catalysts.
[0008] Based on the above research, this invention prepares a Pt3V intermetallic compound catalyst with an atomically ordered structure. With a specific stoichiometric ratio and a periodically ordered Pt-V atomic arrangement, it can significantly modulate the electronic structure of Pt atoms, suppress the adsorption energy of CO at Pt sites, and promote the oxidative removal of CO at adjacent V sites, thus achieving resistance to CO poisoning. This unique ordered alloy structure solves the problem of CO poisoning of Pt sites caused by the long-range disorder of conventional disordered alloys, enhances the CO poisoning resistance of Pt, and lays a material foundation for the engineering application of crude hydrogen PEMFCs.
[0009] Furthermore, the Pt3V ordered intermetallic compound catalyst designed and synthesized in this invention has a fixed stoichiometric ratio, a well-defined structure, and long-range atomic order. The strong 3d-5d orbital coupling effect of the ordered structure can significantly modulate the electronic structure of Pt sites, thereby effectively weakening the adsorption energy of Pt for CO. At the same time, the unique ordered structure of the intermetals can ensure that each Pt site interacts with V atoms, promoting the overflow oxidation of CO and greatly improving the anti-CO poisoning effect of Pt.
[0010] In some embodiments, the platinum source reagent is selected from one or more of potassium chloroplatinate, platinum(II) chloride, and chloroplatinic acid.
[0011] In some embodiments, the vanadium source reagent is selected from one or more of ammonium metavanadate, vanadium oxysulfate, and vanadium chloride.
[0012] In some embodiments, the toner is selected from those with a specific surface area of 250-500 m². 2 / g of toner, such as XC-72R and / or EC-300.
[0013] In some of these implementations, the V:Pt molar ratio is 2-3:1, for example, 2:1 or 3:1.
[0014] In some of these embodiments, the total metal mass fraction is controlled to be 20 to 60 wt%, preferably 20 to 40 wt%, for example 40 wt%.
[0015] In some embodiments, the solvent is water, preferably deionized water.
[0016] In some embodiments, the concentration of Pt in the platinum source reagent in the precursor solution is 0.5-2 g / L, preferably 1 g / L.
[0017] In some embodiments, in the solid precursor preparation step, the precursor solution is heated under negative pressure to evaporate the solvent and obtain a solid precursor. In some implementations of the above steps, the negative pressure condition is 0.01-0.1 MPa, for example, 0.03 MPa; In some embodiments of the above steps, the heating temperature is 40-70°C, for example, 50°C; In some implementations of the above steps, solvent evaporation is performed using a rotary evaporator.
[0018] In some embodiments of the heat treatment step, the temperature of the heat treatment is 670-730°C, preferably 685-715°C, for example 700°C.
[0019] In some embodiments of the heat treatment step, the heat treatment time is 1.5-3 hours, for example, 2 hours.
[0020] In some embodiments of the heat treatment step, the solid precursor is heated to a predetermined heat treatment temperature at a heating rate of 2.5-4°C / min, preferably 2.8-3.5°C / min, for example 3°C / min.
[0021] In some embodiments of the heat treatment step, the heat treatment is carried out under a protective atmosphere, preferably an H2-Ar mixed atmosphere, and more preferably, the volume fraction of H2 in the mixed atmosphere is 2-10%, for example, 5%.
[0022] In some embodiments of the heat treatment step, the heat treatment is followed by natural cooling.
[0023] In some embodiments of the pickling step, the acid is selected from one or more of perchloric acid and sulfuric acid.
[0024] In some embodiments of the pickling step, the concentration of the acid is 0.5-1.5M, for example, 0.5M.
[0025] In some embodiments of the pickling step, the washing time is 4-12 hours, for example, 6 hours.
[0026] In some embodiments of the pickling step, the washing temperature is 50-80°C, for example, 60°C.
[0027] In some embodiments of the pickling step, the drying temperature is 60-90°C, for example, 80°C.
[0028] In some embodiments of the pickling step, the drying time is 8-12 hours, for example, 12 hours.
[0029] On the other hand, the present invention discloses the ordered platinum alloy powder prepared by the above-mentioned method for preparing ordered platinum alloy powder.
[0030] On the other hand, the present invention discloses an ordered platinum alloy powder comprising a carbon skeleton and an intermetallic compound Pt3V distributed on the carbon skeleton, wherein the particle size of the ordered alloy is 3-8 nm, preferably 4-7 nm, for example 5-7 nm.
[0031] In some embodiments, the intermetallic compound Pt3V has a long-range ordered atomic arrangement and a fixed stoichiometry.
[0032] On the other hand, the present invention discloses the use of the above-mentioned ordered platinum alloy powder in the preparation of hydrogen oxidation reaction catalysts, proton exchange membranes and / or fuel cells.
[0033] On the other hand, the present invention discloses a hydrogen oxidation reaction using the above-mentioned ordered platinum alloy powder as a catalyst, and meeting one or more of the following conditions: (1) The CO concentration in the reaction environment is ≥100ppm; (2) The reaction atmosphere is saturated hydrogen gas, and the electrolyte is perchloric acid, preferably 0.1M perchloric acid.
[0034] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0035] The reagents and raw materials used in this invention are all commercially available.
[0036] The positive and progressive effects of this invention are as follows: The ordered platinum alloy powder of the present invention has an ordered intermetallic compound of Pt3V. As a catalyst for hydrogen oxidation reaction (HOR), it significantly enhances the intrinsic activity of Pt for the hydrogen oxidation reaction through electronic structure regulation effect. On the other hand, the ordered atomic structure ensures that Pt sites are coordinated with V, which helps to promote CO overflow and oxidation, improves the anti-CO poisoning effect of Pt, and enhances the tolerance of Pt catalyst to CO concentration. Attached Figure Description
[0037] Figure 1 This is an image of Ordered-Pt3V powder under a spherical aberration electron microscope in Example 1.
[0038] Figure 2 The image shows the Ordered-Pt3V powder under a spherical aberration electron microscope in Comparative Example 2. Detailed Implementation
[0039] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0040] Example 1
[0041] An alloy catalyst is prepared by the following method: 1. Preparation of precursor solution Chloroplatinic acid (H2PtCl6) and vanadium chloride (VCl3) were weighed and dissolved in deionized water, with the molar ratio of V to Pt controlled at 2:1. After the metal precursor was completely dissolved, carbon powder (Vulcan XC-72R, BET specific surface area of about 254 m² / g) was added to ensure that the mass fraction of metal in the subsequent catalyst was about 40 wt%. The above solution was ultrasonically dispersed for 1 h to make the carbon powder uniformly dispersed, thus obtaining the precursor solution.
[0042] The concentration of Pt in the precursor solution of the platinum source reagent chloroplatinic acid is 1 g / L.
[0043] 2. Preparation of solid precursors
[0044] The uniformly dispersed precursor solution was transferred to a rotary evaporator. The vacuum pump was turned on first, and when the vacuum gauge dropped to 0.03 MPa, the rotation speed was set to 60 rpm and the water bath temperature to 50°C. The slurry was evaporated by rotary evaporation to obtain the solid precursor.
[0045] 3. Heat treatment
[0046] The aforementioned solid precursor was placed in a ceramic boat and heat-treated in a high-temperature tube furnace using a H2 (5v / v%)-Ar mixture as a protective gas, and 3 o Heating rate increased to 700 °C / min o The mixture was kept at temperature C for 2 hours, and then allowed to cool naturally to obtain a black powder.
[0047] 4. Pickling
[0048] The black powder obtained from heat treatment was placed in 0.5M dilute sulfuric acid at a temperature of 60°C.o Wash with C for 6 hours, then filter and wash with deionized water until the solution pH is neutral, and dry at 80℃ for 12 hours to obtain ordered alloy (Ordered-Pt3V) powder, which is the alloy catalyst.
[0049] The ordered alloy O-Pt3V powder was characterized, and the results are as follows: Figure 1 show: Figure 1 This is an image of O-Pt3V powder under a spherical aberration electron microscope. The spherical aberration electron microscope can show the ordered arrangement of Pt and V atoms. The brighter atoms are Pt, and the slightly darker ones are V. The bright and dark atoms show a periodic arrangement rather than a random distribution, which proves that an ordered Pt3V intermetallic compound structure has been formed.
[0050] Example 2
[0051] An alloy catalyst was prepared using a method similar to that of Example 1, except that the molar ratio of V to Pt was controlled at 3:1 in the precursor solution preparation step. Aberration-corrected electron microscopy showed that this example yielded an ordered alloy powder, but with a slightly lower degree of ordering.
[0052] Comparative Example 1
[0053] A catalyst was prepared using a method similar to that in Example 1, except that: in the precursor solution preparation step, only chloroplatinic acid and carbon powder were added, without vanadium chloride; and in the heat treatment step, the holding temperature was adjusted to 200°C. o C, with all other conditions remaining unchanged. The final catalyst obtained is a Pt / C catalyst.
[0054] Comparative Example 2
[0055] An alloy catalyst was prepared using a method similar to that in Example 1, except that the molar ratio of V to Pt was controlled at 1:1 in the precursor solution preparation step.
[0056] The obtained ordered alloy powder spherical aberration electron micrographs are shown below. Figure 2 As shown, this embodiment yielded an ordered alloy powder.
[0057] Comparative Example 3
[0058] An alloy catalyst was prepared using a method similar to that of Example 1, except that the temperature was raised to 800°C and then held at that temperature during the heat treatment step. Aberration-corrected electron microscopy showed that an ordered alloy powder was prepared in this example.
[0059] Comparative Example 4
[0060] An alloy catalyst was prepared using a method similar to that in Example 1, except that the temperature was raised to 600°C and then held at that temperature during the heat treatment step. The resulting catalyst was examined using aberration-corrected electron microscopy, and the results showed that the catalyst was a disordered alloy catalyst.
[0061] Comparative Example 5
[0062] An alloy catalyst was prepared using a method similar to that in Example 1, except that the temperature was raised to 500°C and then held at that temperature during the heat treatment step. The resulting catalyst was examined using aberration-corrected electron microscopy, and the results showed that the catalyst was a disordered alloy catalyst.
[0063] Comparative Example 6
[0064] An alloy catalyst was prepared using a method similar to that of Example 1, except that the heating rate in the heat treatment step was 2°C. Aberration-corrected electron microscopy showed that an ordered alloy powder was prepared in this example.
[0065] Comparative Example 7
[0066] An alloy catalyst was prepared using a method similar to that of Example 1, except that the heating rate in the heat treatment step was 5°C. Aberration-corrected electron microscopy showed that this example yielded an ordered alloy powder, but the degree of ordering was somewhat reduced.
[0067] Experimental Example
[0068] This experimental example tests the performance of the catalysts prepared in the above examples and comparative examples.
[0069] I. Catalyst Size
[0070] 1. Method
[0071] The particle size of the catalysts prepared in the comparative examples was detected by transmission electron microscopy. The procedure was carried out in accordance with conventional methods, such as: the powder sample was ultrasonically dispersed and then dropped onto a copper mesh support film for drying. Multiple images with different fields of view were taken under the transmission electron microscope. The equivalent circle diameter or Freette diameter of the particles was automatically measured using software such as ImageJ. Finally, the average particle size was calculated by the particle size distribution histogram.
[0072] 2. Results
[0073] The particle size results of the catalysts prepared in the examples and comparative examples are shown in the table below.
[0074] Table 1. Average particle size of catalysts
[0075] Note: "~" indicates approximately, meaning the center value is rounded to one decimal place, and the tolerance interval half-width is rounded to two decimal places.
[0076] II. Anti-toxic
[0077] 1. Method
[0078] HOR (Hydrotoxicity resistance) tests were performed using a rotating disk electrode (RDE) system in a 0.1 M HClO4 solution with a three-electrode system. A CO / H2 mixture containing a small amount of CO (100 ppm CO concentration) was introduced, and the CO tolerance current density was measured using polarization curves to evaluate the anti-poisoning properties.
[0079] 2. Results
[0080] The current density of different catalysts at a constant potential of 0.2 V was tested, and the results are shown in the table below.
[0081] Table 2. CO withstand current density conditions
[0082] Note: "~" indicates approximately, meaning the center value is rounded to one decimal place, and the tolerance interval half-width is rounded to two decimal places.
[0083] The above results indicate that the ordered platinum alloy powder obtained by the preparation method of the present invention has better CO tolerance, while the Pt / C catalyst obtained in Comparative Example 1 has poor CO tolerance. The catalysts obtained in Comparative Examples 2-7 also have poor CO tolerance due to poor raw material composition or poor preparation process.
Claims
1. A method for preparing ordered platinum alloy powder, characterized in that, Includes the following steps: Precursor solution preparation: Vanadium source reagent and platinum source reagent are dissolved in solvent at a V:Pt molar ratio of 1.5-3.5:1, carbon powder is added and dispersed evenly to obtain the precursor solution; Preparation of solid precursor: The solvent of the precursor solution is recovered to obtain a solid precursor; Heat treatment: The solid precursor is heated at 650-750°C. o Heat treatment at C for 1-4 hours yields powder; Pickling: The heat-treated powder is washed in acid, rinsed with water until neutral, and dried to obtain the ordered platinum alloy powder.
2. The method for preparing ordered platinum alloy powder as described in claim 1, characterized in that, In the precursor solution preparation step, one or more of the following conditions are met: (1) The platinum source reagent is selected from one or more of potassium chloroplatinate, platinum chloride, and chloroplatinic acid; (2) The vanadium source reagent is selected from one or more of the following: ammonium metavanadate, vanadium oxysulfate, and vanadium chloride; (3) The toner is selected from those with a specific surface area of 250-500 m². 2 / g of toner, such as XC-72R and / or EC-300; (4) The molar ratio of V:Pt is 2-3:1, for example, 2:1 or 3:1; (5) The total metal mass fraction is controlled to be 20~60wt%, preferably 20~40wt%, for example 40wt%; (6) The solvent is water, preferably deionized water; (7) The concentration of Pt in the platinum source reagent in the precursor solution is 0.5-2 g / L, preferably 1 g / L.
3. The method for preparing ordered platinum alloy powder as described in claim 1, characterized in that, In the solid precursor preparation step, the precursor solution is heated under negative pressure to evaporate the solvent and obtain the solid precursor. Preferably, one or more of the following conditions are met: (1) The negative pressure condition is 0.01-0.1 MPa, for example, 0.03 MPa; (2) The heating temperature is 40-70℃, for example, 50℃; (3) Solvent evaporation is carried out using a rotary evaporator.
4. The method for preparing ordered platinum alloy powder as described in claim 1, characterized in that, In the heat treatment step, one or more of the following conditions must be met: (1) The temperature of the heat treatment is 670-730℃, preferably 685-715℃, for example 700℃; (2) The heat treatment time is 1.5-3 hours, for example, 2 hours; (3) The solid precursor is heated to a predetermined heat treatment temperature at a heating rate of 2.5-4℃ / min, preferably 2.8-3.5℃ / min, for example 3℃ / min; (4) The heat treatment is carried out under a protective atmosphere. Preferably, the protective atmosphere is an H2-Ar mixed atmosphere. More preferably, the volume fraction of H2 in the mixed atmosphere is 2-10%, for example, 5%. (5) After the heat treatment, the temperature is allowed to drop naturally.
5. The method for preparing ordered platinum alloy powder as described in claim 1, characterized in that, In the pickling step, one or more of the following conditions must be met: (1) The acid is selected from one or more of perchloric acid and sulfuric acid; (2) The concentration of the acid is 0.5-1.5M, for example, 0.5M; (3) The washing time is 4-12 hours, for example, 6 hours; (4) The washing temperature is 50-80℃, for example, 60℃; (5) The drying temperature is 60-90℃, for example, 80℃; (5) The drying time is 8-12h, for example 12h.
6. The ordered platinum alloy powder prepared by the method according to any one of claims 1-5.
7. An ordered platinum alloy powder, characterized in that, The ordered alloy comprises a carbon skeleton and an intermetallic compound Pt3V distributed on the carbon skeleton, and the particle size of the ordered alloy is 3-8 nm, preferably 4-7 nm, for example 5-7 nm.
8. The ordered platinum alloy powder as described in claim 7, characterized in that, The intermetallic compound Pt3V has a long-range ordered atomic arrangement and a fixed stoichiometric ratio.
9. Use of the ordered platinum alloy powder according to any one of claims 6-8 in the preparation of hydrogen oxidation reaction catalysts, proton exchange membranes and / or fuel cells.
10. A hydrogen oxidation reaction, characterized in that, The ordered platinum alloy powder according to any one of claims 6-8 is used as a catalyst, and one or more of the following conditions are met: (1) The CO concentration in the reaction environment is ≥100ppm; (2) The reaction atmosphere is saturated hydrogen gas, and the electrolyte is perchloric acid, preferably 0.1M perchloric acid.
